2019
DOI: 10.1371/journal.pmed.1002860
|View full text |Cite
|
Sign up to set email alerts
|

Care practices and neonatal survival in 52 neonatal intensive care units in Telangana and Andhra Pradesh, India: A cross-sectional study

Abstract: Background The Indian government supports both public- and private-sector provision of hospital care for neonates: neonatal intensive care is offered in public facilities alongside a rising number of private-for-profit providers. However, there are few published reports about mortality levels and care practices in these facilities. We aimed to assess care practices, causes of admission, and outcomes from neonatal intensive care units (NICUs) in public secondary and private tertiary hospitals and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
13
1
2
Order By: Relevance
“…12,13,19 However, lower percentages of neonatal sepsis were reported in Islamabad, Pakistan, Kano and Enugu state in Nigeria, Haryana, Bohal, Telangana and Andhra Pradesh and Maharashtra in India, Addis Ababa in Ethiopia and Tehran in Iran. 10,[22][23][24][25][26][29][30][31] On the contrary, higher percentages compared to our result were pointed out by a number of studies, for example; studies conducted in different parts of Ethiopia reported that sepsis is the most common cause of admission to the NICU and it represented 40.5%, 67.9% and 78.4% of admission diagnosis in eastern Ethiopia, northwest Ethiopia and Adama respectively. 4,15,16 Moreover, a study in south Sudan, showed that sepsis is the leading cause of admission with a 63.7% morbidity rate, and another study in Benin city in Nigeria reported sepsis to be the causes of admission of 38.6% (n=??)…”
Section: Neonatal Morbiditycontrasting
confidence: 69%
See 3 more Smart Citations
“…12,13,19 However, lower percentages of neonatal sepsis were reported in Islamabad, Pakistan, Kano and Enugu state in Nigeria, Haryana, Bohal, Telangana and Andhra Pradesh and Maharashtra in India, Addis Ababa in Ethiopia and Tehran in Iran. 10,[22][23][24][25][26][29][30][31] On the contrary, higher percentages compared to our result were pointed out by a number of studies, for example; studies conducted in different parts of Ethiopia reported that sepsis is the most common cause of admission to the NICU and it represented 40.5%, 67.9% and 78.4% of admission diagnosis in eastern Ethiopia, northwest Ethiopia and Adama respectively. 4,15,16 Moreover, a study in south Sudan, showed that sepsis is the leading cause of admission with a 63.7% morbidity rate, and another study in Benin city in Nigeria reported sepsis to be the causes of admission of 38.6% (n=??)…”
Section: Neonatal Morbiditycontrasting
confidence: 69%
“…Generally, it was estimated that 10% of newborn babies are expected to develop jaundice that need clinical treatment. 10,11,21,24,26,[30][31][32] Bilirubin-induced mortality was among the top causes of death in the ten countries with the highest mortality rates globally. 32 In contrast to the other cause of morbidities, most of the neonatal jaundice is unpreventable.…”
Section: Neonatal Morbiditymentioning
confidence: 99%
See 2 more Smart Citations
“…The study site was two Indian states of Telangana and Andhra Pradesh, which have a slightly better socio-economic situation than India’s average [ 12 ]. The 60 participating hospitals included 28 public secondary hospitals, 6 public medical colleges, 20 private tertiary hospitals and 6 private medical colleges with high neonatal mortality rates as described elsewhere [ 19 ]. We included women seeking childbirth care and neonates admitted to NCUs.…”
Section: Methodsmentioning
confidence: 99%